Genetic Evidence Supporting the Role of the Calcium Channel, CACNA1S, in Tooth Cusp and Root Patterning - Laugel-Haushalter, Virginie; Morkmued, Supawich; Stoetzel, Corinne; Geoffroy, Véronique; Muller, Jean; Boland, Anne; Deleuze, Jean-François; Chennen, Kirsley; Pitiphat, Waranuch; Dollfus, Hélène; Niederreither, Karen; Bloch-Zupan, Agnès; et al. (Frontiers in Physiology, 2018)
In this study, we report a unique dominantly inherited disorganised supernumerary cusp and single root phenotype presented by 11 affected individuals belonging to 5 north-eastern Thai families. Using whole exome sequencing (WES) we identified a common single missense mutation that segregates with the phenotype in exon 6 of CACNA1S (Cav1.1) (NM_000069.2: c.[865A>G];[=] p.[Ile289Val];[=]), the Calcium Channel, Voltage-Dependent, L Type, Alpha-1s Subunit, OMIM 114208), affecting a highly conserved amino-acid isoleucine residue within the pore forming subdomain of CACNA1S protein. This is a strong genetic evidence that a voltage-dependent calcium ion channel is likely to play a role in influencing tooth morphogenesis and patterning.